Association between objective neurocognitive functioning and neurocognitive complaints in recurrent high-grade glioma: Longitudinal evidence of cognitive awareness from EORTC brain tumour trials - Caramanna, Ivan; Reijneveld, Jaap C.; van de Ven, Peter M.; van den Bent, Martin; Idbaih, Ahmed; Wick, Wolfgang; Taphoorn, Martin J. B.; Dirven, Linda; Bottomley, Andrew; Klein, Martin (European journal of cancer, 2023)
Background - Patients’ reduced awareness of neurocognitive functioning (NCF) may negatively affect the reliability of patient-reported outcomes (PROs) and clinical decision-making. This study evaluated cognitive awareness, defined as the association between NCF and neurocognitive complaints, over the disease course of patients with recurrent high-grade glioma (HGG). - Methods - We assessed NCF using the EORTC core clinical trial battery and neurocognitive complaints using the Medical Outcome Study questionnaire. Patients were categorised as impaired or intact, based on their neurocognitive performance. Spearman’s rank correlations were calculated between NCF and neurocognitive complaints at baseline and each 12 weeks, until 36. The association between changes in NCF and neurocognitive complaints scores between these follow-up assessments was determined using Pearson’s correlation. - Results - A total of 546 patients were included. Neurocognitively impaired patients (n = 437) had more neurocognitive complaints (range: 10.51 [p < 0.001] to 13.34 [p = 0.001]) than intact patients (n = 109) at baseline, at 12 and 24 weeks. In intact patients, NCF and neurocognitive complaints were correlated for only one domain at baseline (0.202, p = 0.036), while in impaired patients correlations were more frequently found in various domains and time points (range: 0.164 [p = 0.001] to 0.334 [p = 0.011]). Over the disease course, NCF and neurocognitive complaints were correlated for only one domain at baseline (0.357, p = 0.014) in intact patients while in impaired patients they were correlated for more domains and time points (range: 0.222 [p < 0.001] to 0.366 [p < 0.001]). - Conclusion - Neurocognitively impaired patients with recurrent HGG are aware of their neurocognitive limitations at study entry and during follow-up, which should be considered in clinical decision-making and when interpreting PRO results.